EFFECT OF SHOOT PRUNING INTERVAL AND DOSAGE OF POTASSIUM FERTILIZER ON GROWTH AND YIELD OF YAM BEAN (PACHYRHIZUS EROSUS L.) - Munandar, Denna Eriani; Saputra, Yusuf; Pradana, Ankardiansyah Pandu (International Journal of Research -GRANTHAALAYAH, 2023)
A study was conducted in Baratan village, district of Patrang, Jember, East Java, on the effects of shoot pruning intervals and potassium fertilizer dosages on the growth and yield of yam bean (Pachyrhizus erosus L.). Pruning of the plant shoot was done six weeks after planting, 50 cm above the soil surface. Three levels of shoot pruning treatment were: no pruning (control), shoot pruning every 7 days, and shoot pruning every 14 days. The dosages of potassium fertilizer were: 0, 75, 150, 225, and 300 kg ha1 of K2O. The experimental design adopted was the completely randomized block design (CRBD) with three replications. The results showed that pruning of shoots every 7 days with potassium fertilizer at 225 kg ha-1 gave the best effect on leaf area index, tuber diameter, tuber fresh weight, tuber dry weight, and total plant fresh weight and dry weight, respectively. Those values were 6.1; 18.88 cm; 468.56 g, 89.05 g, 710.32 g, and 143.54 g, respectively. There was an increase of 289, 175, 392, 362, 247, and 223 percent again without pruning and potassium fertilizer (control) treatments. Pruning shoots every 7 days with 300 kg ha-1 potassium fertilizer resulted in the highest tuber carbohydrate content, which was 44.99 percent higher than the control treatment (no pruning and potassium fertilizer application).